Factors of Consumer Behavior of Ukrainian Households in the Pre-War and War Period: a Collective Approach to Definition and Evaluation - Kotenko, T. M.; Korotkova, D. S. (Statistics of Ukraine, 2023)
The development and implementation of an effective socio-economic policy requires various statistical data on the current economic performance. An important set of statistical data pertains to characteristics of the consumer behavior of households. Analysis and systematization of the factors and structural change in the consumer behavior of households, along with determining and evaluating their reactions on such crises, have become important considering the shocks experienced by Ukraine in the recent time. The research objective is to describe the changes in the pattern of household consumption, to determine, systematize and estimate the existing exogenous and endogenous factors in the context of geopolitical change. The research novelty consists in determining the vector of change in the consumer behavior of Ukrainian households in view of current events and crises in Ukraine and the world, especially ones related with the Russian-Ukrainian war and the pandemic of COVID-19, and in constructing the authors’ model for households’ behavior in time of war with account to the factor of time. The main features of the consumer behavior of Ukrainian households over longer than 20 latest years were identified. The consumer behavior of the Ukrainian population was analyzed during the crisis of COVID-19 at country level and by size and gender of a person in working age (18–59 years) who heads the household. It was concluded that consumer spending on essential goods increased in the first year of the pandemic and sharply decreased in the second year, with demonstrating that the consumer reaction on this crisis was quite similar to other ones. The current consumer behavior of Ukrainian households was analyzed, with identifying and estimating the influence of exogenous and endogenous factors on the vector of its change. The results of the study allow or a more detailed assessment of the consumer behavior of Ukrainian households in time of crises and a better understanding of its features in general.